Vitamin D metabolism in the premature newborn: A randomized trial. Issue 4 (August 2016) - Hanson, Corrine; Jones, Glenville; Lyden, Elizabeth; Kaufmann, Martin; Armas, Laura; Anderson-Berry, Ann
Summary: Background & aims: Vitamin D status during infancy has been associated with important pediatric health outcomes; however concentrations of many vitamin D metabolites in premature infants are not yet described. The objective of this study was to evaluate concentrations of 25(OH)D3, 24, 25(OH)2 D3, and 3-epi-25(OH)D3 in premature infants. Methods: 32 infants <32 weeks gestation were randomized to receive 400 or 800 IU/day of vitamin D3 orally. Vitamin D metabolites from serum obtained monthly were analyzed in triplicate using a novel, very sensitive Liquid Chromatography-Tandem Mass Spectrometry-based method. Statistical analysis was conducted using the Fisher's exact test, Wilcoxon Rank Sum test, and Spearman correlation coefficients. Measurements over time were fit with linear mixed effect models. A p-value of <0.05 was considered statistically significant. Results: Mean serum 25(OH)D3 concentrations in cord blood were 17.3 ng/mL; mean 3-epi-25(OH)D3 were 1.3 ng/mL, mean 24, 25(OH)2 D3 were 1.4 ng/mL. Both 25(OH)D3 and 3-epi-25(OH)D3 increased significantly over time, and the percent of total 25(OH)D3 concentration that was 3-epi-25(OH)D3 also increased significantly (7.2% vs. 29.7%, p < 0.0001 for cord blood vs. 8 weeks). Serum 25(OH)D3 :24, 25(OH)2 D3 ratios at weeks 4 and 8 were higher than ratios reported in older children and adults. Conclusion: Vitamin D metabolism in infants appears to have distinct differences from adults. Vitamin D supplementation was effective in raising 25(OH)D3 concentrations; however significant increases in 3-epi-25(OH)D3 also occurred. Increased 25(OH)D3 : 24, 25(OH)2 D3 ratios in premature infants may be due to immature expression of CYP24A1. Further work is necessary to determine if there are developmental advantages to this unique vitamin D metabolism.